MDMA for the treatment of misophonia, a proposal - Webb, Jadon; Keane, Shannon (Frontiers in Psychiatry, 2022)
Misophonia is a disorder characterized by negative physical and emotional reactions to certain trigger sounds, such as chewing food. Up to 50% of population samples endorse some symptoms of misophonia, with about 20% having symptoms that impair normal life functioning. Most misophonia patients exhibit intense negative emotions and autonomic arousal (the fight-flight-freeze response) in response to a trigger, similarly to how someone with post-traumatic stress disorder (PTSD) might respond to a trauma trigger. Curiously, misophonia trigger sounds are often most distressing when coming from a specific person, suggesting the disorder may be responsive to interpersonal relationship factors. Treatment of misophonia is currently limited to the use of hearing modifications (e.g. earplugs or headphones) and psychotherapy, but many patients continue to suffer despite these best efforts. Phase 3 clinical trials suggest that MDMA is effective at treating the symptoms of autonomic arousal, negative emotions, and interpersonal suffering found in PTSD. As such, we propose that MDMA may represent an ideal treatment for some suffering from severe misophonia. In this perspective article, we review the symptoms of misophonia, and outline how MDMA may be uniquely suited for treating it, perhaps using a protocol analogous to the MAPS Phase 3 studies for PTSD.